PRECISION HOLISTIC NURSING CARE FOR CARDIOVASCULAR DISEASE: ENHANCING PSYCHOLOGICAL WELL-BEING, SPIRITUAL HEALTH, AND CLINICAL OUTCOME - Aris Citra Wisuda; Citra Suraya; Dilgu Meri; Atma Deviliawati; Santi Rosalina; Heriziana Hz (Journal Of Nursing Science Research, 2026)
Cardiovascular disease is a major cause of morbidity and is frequently accompanied by psychological and spiritual distress, adversely affecting clinical stability, treatment adherence, and quality of life. Precision Holistic Nursing Care, an individualized nursing approach integrating psychological support, Islamic spiritual care, clinical education, relaxation therapy, hemodynamic monitoring, and therapeutic assistance tailored to patient needs, may help address these multidimensional challenges. This study aimed to examine changes in psychological, spiritual, and clinical outcomes following the implementation of Precision Holistic Nursing Care among patients with cardiovascular disease. Aquasi-experimental pretest–posttest study without a control group was conducted at Siti Khadijah Islamic Hospital Palembang from January to April 2026. Forty-four patients were recruited through purposive sampling. Anxiety, depression, and spiritual well-being were assessed using the Hamilton Anxiety Rating Scale (HARS), Beck Depression Inventory-II (BDI-II), and Spiritual Well-Being Scale (SWBS). Clinical outcomes included blood pressure, pulse rate, respiratory rate, sleep quality, and treatment adherence. Data were analyzed using paired t-tests (p < 0.05). Following the intervention, anxiety scores decreased from 28.91 ± 5.84 to 18.77 ± 4.96 (p < 0.001; d = 1.74), while depression scores declined from 22.45 ± 6.18 to 14.36 ± 5.21 (p < 0.001; d = 1.39). Spiritual well-being improved, with spiritual calmness increasing from 38.6% to 84.1% and confidence in coping with illness from 43.2% to 79.5%. Clinical indicators also improved, including blood pressure (152.6 ± 14.8 to 139.4 ± 12.7 mmHg), pulse rate (96.2 ± 10.5 to 84.7 ± 8.9 beats/minute).